1974
DOI: 10.1111/j.1432-1033.1974.tb03413.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Lipid Metabolism in Adipose‐Tissue Hornogenates of Fasted Refed Rats

Abstract: 1.The 700 x g fat-poor internatant from epididymal adipose tissue homogenate of fasted refed rats was incubated a t pH6.5 with 0.5mM [1-l4C]acetate in the presence of cofactors. After incubation, six lipid classes were separated by thin-layer chromatography and their fatty acids analyzed by radio gas-liquid chromatography. The incorporation of [ 1 -14C]acetate into glycerides was limited by the activity of acetyl-CoA carboxylase, and was stimulated two to three-fold by the addition of 0.1 mM unlabelled malonyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1975
1975
1979
1979

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
(7 reference statements)
1
13
0
Order By: Relevance
“…The results of the direct assay of stearic acid desaturase reported in this paper demonstrate that the increased incorporation of precursors into palmitoleic acid and oleic acid observed by Christophe's group in whole-tissue preparations from obese mice are due, at least in part, to an increase in the fatty acid desaturase system (Winand et al, 1968(Winand et al, , 1969a(Winand et al, , 1973. The threefold increase in the activity of stearic acid desaturase on a protein basis is similar to the increase in citrate cleavage enzyme (Komacker & Lowenstein, 1964) acetyl-CoA carboxylase and fatty acid synthetase (Chang et al, 1967) in livers from 12-week-old obese-hyperglycaemic mice compared with lean mice.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The results of the direct assay of stearic acid desaturase reported in this paper demonstrate that the increased incorporation of precursors into palmitoleic acid and oleic acid observed by Christophe's group in whole-tissue preparations from obese mice are due, at least in part, to an increase in the fatty acid desaturase system (Winand et al, 1968(Winand et al, , 1969a(Winand et al, , 1973. The threefold increase in the activity of stearic acid desaturase on a protein basis is similar to the increase in citrate cleavage enzyme (Komacker & Lowenstein, 1964) acetyl-CoA carboxylase and fatty acid synthetase (Chang et al, 1967) in livers from 12-week-old obese-hyperglycaemic mice compared with lean mice.…”
Section: Discussionmentioning
confidence: 77%
“…The only consistent change in fatty acid composition, however, is an increase in the proportion of palmitoleic acid (Haessler & Crawford, 1965;Stein et al, 1967;Winand et al, 1969b;Bullfield, 1972) with a compensatory small decrease in several fatty acids but mainly linoleic acid. The obese strains show both a high capacity to deposit dietary fat (Lemonnier et al, 1971) and a higher lipogenic capacity (for a review see Bray & York, 1971), which may maintain the fatty acid composition near normal since mouse diets usually contain a lower proportion of oleic acid than linoleic acid, the reverse of the proportions in adipose tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Injection of insulin also increases the activity in livers of normal rats (Inkpen et al, 1969). Increased synthesis of palmitoleic acid and oleic acid has been demonstrated in the liver and adipose tissue of obese-hyperglycaemic (ob/ob) mice (Winand et al, 1968(Winand et al, , 1969a(Winand et al, ,b, 1973 and it has been confirmed that this occurs through an increase in the activity of the desaturase enzyme system (Enser, 1975). Since obese mice are markedly hyperinsulinaemic (Stauffacher et al, 1967;Christophe et al, 1959) this seemed a likely cause of the increased desaturase activity.…”
mentioning
confidence: 99%
“…Polyunsaturated fatty acids decrease and saturated fatty acids increase the desaturase activity. Since the carcass lipids of obese mice contain lower proportions of polyunsaturated fatty acids than lean mice (Haessler & Crawford, 1965;Stein et al, 1967;Winand et al, 1969b;Bullfield, 1972), the increased desaturase activity might be explained by a decrease in their inhibitory activity. Food intake also regulates A9-desaturase activity (Inkpen et al, 1969;Lee & Sprecher, 1971) with a decrease during starvation and an increase to Vol.…”
mentioning
confidence: 99%